Quality Changes of ‘Unpad CB2’ Red Chili Pepper at Different Ozone Concentrations and Storage Periods - Kusumiyati Kusumiyati; Lestari Rahma W.; Mubarok Syariful (Journal of Horticultural Research)
Red chili pepper, a popular and versatile horticultural commodity, is typically consumed fresh. This fruit has a relatively short storage period, during which its quality decreases. One potential method to maintain the quality of red chili pepper is postharvest ozonation. This study aimed to determine the effect of different ozone concentrations and storage periods on the quality changes of ‘Unpad CB2’ red chili pepper. The method used was a factorial randomized block design with two factors: ozone concentrations (0, 0.5, 1, 1.5, and 2 ppm) and storage periods (0, 7, and 14 days). The results showed an interaction between ozone concentrations and storage period on quality parameters such as water content, fruit firmness, total carotenoid content, antioxidant activity and capacity. Ozone concentration of 1.5 ppm with a storage period of 14 days gave better quality results than other treatments. The 1.5 ppm concentration significantly increased the content of capsaicin, dihydrocapsaicin, total capsaicinoids, and total phenolics, and also increased the value of texture and Scoville heat units.